You are on page 1of 19

NON

HOMOGENEOUS
LINEAR EQUATIONS
In this Topic we will discus the general solution of
Linear DE with constant coefficient f(D)y = F(x)
The solution of the reduced (or homogeneous)
equation f(D)= 0 is denoted by yc and is called
Complimentary Function (C F). It is the general
solution of the reduced equation.

1
The function y p = [ F ( x )] is called
f ( D)
1
particular Integral (P I) where is the
inverse operator of f(D). f ( D)
Since y p is any particular solution, therefore it
does not contain any constant
Theorem
If yc is the Complimentary Function (C. F) and y p
Particular Integral (P. I) of the equation
f(D)y = F(x)

then y= y +y c p
Is called the General Solution.
When a differential equation is of higher
order is of the form
f(D)y = F(x)
then Particular Integral (P. I) depends upon the
nature of F(x).
WORKING RULE
FOR FINDING P I
Following cases will be discussed:-
a. F(x) = eax ,
1 1 ax
then yp = e =
ax
e
f ( D) f (a )
provided f(a) is non-zero. However, if f(a) = 0,
then
1 1
yp = x / e =x /
ax
e ax

f ( D) f (a )

If still f/(a) = 0, then we repeat the above


process till the time we get a non-zero
denominator.
b. If F(x) = sin ax or cos ax, then we have two
alternate methods:-
cos ax 1
1. y p = = iax
Re(e ) and
f ( D) f ( D)
sin ax 1
yp = = iax
Im( e )
f ( D) f ( D)
and then proceed as in rule 2a.
cos ax cos ax cos ax
2. yp = = =
f ( D ) g( D ) g( −a )
2 2

provided g(-a2) is non-zero


However, if g(-a2 ) = 0, then
1 1
yp = x / cosax = x 2
cosax
f ( D) h( D )
1
=x cosax
h( − a )
2

If still h(-a2 ) = 0, then we repeat the above


process till the time we get a non-zero
denominator. Case for sin ax is similar.
c. If F(x) = eax cos bx, then
e ax cos bx 1
yp = =e ax
cos bx
f ( D) f ( D + a)
and proceed as in para 2 b. This method is
known as “Exponential Shift”.
d. If F(x) = f(x), then
f ( x) −1
yp = = [ f ( D )] f ( x )
f ( D)
we expand finitely the negative exponent by
Binomial Theorem and apply operators on
f(x).
Solve d y 2
dy
2
− 3 + 2y = e + e
x 2x

dx dx
Soln: Here f(D) = D2 - 3D + 2 and characteristic
equation m2 - 3m + 2 = 0 has roots 1 and 2.
Therefore yc = c1 ex + c2 e2x ………(i)
For P.I
e +ex
e2x
e x 2x
yp = 2 = 2 + 2
D − 3D + 2 D − 3D + 2 D − 3D + 2
x 2x
e e
=x +x = − xe + xe
x 2x
...(ii)
2D − 3 2D − 3
So general solution is y = yc + yp
y = c1 ex + c2 e2x - x ex + x e2x
3 2
d y d y dy
Solve 3
− 2 + − y = 4 sin x
dx dx dx
Soln: Here f(D) = D3 - D2 + D - 1 and the
characteristic equation
m3 - m2 + m – 1 = 0 has roots 1 and ± i
Therefore
yc = c1 ex + c2 cos x + c3 sin x ……(i)
For P.I
4 sin x 4 sin x
yp = 3 =x
D − D + D−1
2
3D − 2D + 1
2

4 sin x
=x (Using D = −1)
2

− 3 − 2D + 1
4 sin x ( D − 1) sin x
=x = −2 x
− 2( D + 1) D −1
2

= x (cos x − sin x ) ………………(ii)

From (i) & (ii) General Solution is y = yc + yp


= c1 ex+ c2 cos x + c3 sin x + x (cos x – sin x)
Solve 2
d y dy
2
− 2 + 4 y = e cos x
x

dx dx
Soln: Here f(D) = D2 - 2D + 4 and characteristic
equation m2 – 2m + 4 = 0 has roots1 ± i 3
Therefore yc = ex (c1 cos x + c2 sin x)………(i)
For P.I
e x cos x cos x
yp = 2 =e x

D − 2D + 4 ( D + 1) 2 − 2( D + 1) + 4
(by the application of exponential shift)
cos x x cos x 1 x
=e x
=e = e cos x …….(ii)
D +3
2
−1+ 3 2
cos x x cos x 1 x
=e x
=e = e cos x
D +3
2
−1+ 3 2
From (i) & (ii) the General Solution
y = yc + yp
= ex (c1 cos x + c2 sin x)
Solve 3
d y dy
3
− 7 − 6 y = e + xe
2x 2x

dx dx
Soln: Here f(D) = D3 - 7D - 6 and characteristic
equation m3 – 7m - 6= 0 has roots -1, -2 and
3. Therefore yc = c1 e-x + c2 e-2x + c3 e3x
………(i)e 2 x + xe 2 x e2x xe 2 x
= 3
y pP.I
For = 3 + 3
D − 7D − 6 D − 7D − 6 D − 7D − 6
e2x x
= +e 2x

( 2) − 7( 2) − 6
3
( D + 2) 3 − 7( D + 2) − 6
1 2x x
=− e +e 2x

12 D + 6 D + 5 D − 12
3 2
1 2x x
= − e + e2x
12  D + 6D + 5D 
3 2
− 12 1 − 
 12 
−1
1 2 x 1 2 x  D + 6D + 5D 
3 2
= − e − e 1 −  ( x)
12 12  12 
1 2x 1 2x  D + 6D + 5D 
3 2
= − e − e 1 + ( x )
12 12  12 
1 2x 1 2x  5
= − e − e x + 
12 12  12 
1 2x 1 5 2x
=− e − xe −
2x
e
12 12 144
17 2 x 1
=− e − xe 2x
……………..(ii)
144 12
From (i) & (ii) the General Solution

y = yc + yp
17 2 x 1
= c1 e-x + c2 e-2x + c3 e3x − e − xe 2 x
144 12
Solve 2
d y dy
2
− 4 + 13 y = 8 sin 3 x
dx dx
Soln: Here f(D) = D2 - 4D + 13 and characteristic
equation m2 – 4m +13 = 0 has roots2 ± 3i
Therefore
yc = e2x (c1 cos 3 x + c2 sin3 x)………(i)
For P.I 8 sin 3 x sin 3 x
yp = 2 =8
D − 4 D + 13 − 9 − 4 D + 13
sin 3 x ( D + 1) sin 3 x 3 cos 3 x + sin 3 x
= −2 = −2 = −2
D−1 D −1
2
−9−1
1
= ( 3 cos 3 x + sin 3 x ) ……………..(ii)
5
From (i) & (ii) the General Solution

y = yc + yp

= e2x (c1 cos 3 x + c2 sin3 x)


1
+ ( 3 cos 3 x + sin 3 x )
5 …………(iii)

Using y =1 at x = 0 in eq (iii) we get c1 = 2/5


Also from eq (iii)
y/ = 2 e2x (c1 cos 3x + c2 sin 3x)
+ e2x (-3c1 sin 3x + 3c2 cos 3x)
9 3
− sin 3 x + cos 3 x …………..(iv)
5 5
Using y/ = 2 at x = 0 in eq (iv) we get c2 = 1/5
Using the values of c1 and c2 in eq (iii) we get
2x
e 1
y= [ 2 cos 3 x + sin 3 x ] + [sin 3 x + 3 cos 3 x ]
5 5